Annealing Temperature Effects on Humidity Sensor Properties for Mg0.5W0.5Fe2O4 Spinel Ferrite - Iulian Petrila; Florin Tudorache (Sensors, 2022)
The effects of annealing temperature on the structural, physical and humidity sensing properties of stoichiometric Mg0.5W0.5Fe2O4 spinel ferrite are investigated. In order to highlight the influence of sintering temperature on the structural, magnetic and electrical properties, ferrite samples were sintered for 2 h at 850 °C, 900 °C, 950 °C, 1000 °C and 1050 °C and the physical properties and humidity influence on magnesium-tungsten ferrite materials were analyzed. X-ray diffraction investigations confirmed the formation of magnesium-tungsten ferrite in the analyzed samples. SEM micrographs revealed the influence of annealing temperature on the microstructures of the samples and provided information related to their porosity and crystallite shape and size. This material, treated at different temperatures, is used as an active element in the construction of capacitive and resistive humidity sensors, whose characteristics were also investigated in order to determine the most suitable sintering temperature.